Progressive biological characteristics changes of Aedes albopictus (Skuse) (Diptera: Culicidae) in hot spot and non-hot spot areas at Subang Jaya Municipality / Muhammad Afiq Zaki ... [et al.] - Zaki, Muhammad Afiq; Shari, Norshafarina; Ismail, Rodziah; Hassan, Hamzah Fansuri; Mohd Yatim, Siti Rohana (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Dengue fever is a complex disease caused by bites of infected female Aedes mosquitoes. The existence of hot spot (HS) area increases as the number of dengue cases reported increase every week. Repeated chemical control application implemented in hot spot areas is expected to affect the normal life cycle of the mosquitoes. This study was carried out to compare the differences between biological characteristics of Aedes albopictus in HS and non-hot spot (NHS) areas in the context of chemical application. Ovitraps were set up at both HS and NHS areas in Subang Jaya Municipality. Throughout this study on biological characteristics, namely duration of immature stages, gonotrophic cycle, fecundity (number of eggs) and longevity were observed under laboratory controlled conditions. Ae. albopictus from HS areas demonstrated shorter duration, 6 days than NHS, 10 days in immature stages (p = 0.001). While, for longevity, longer days is observed in HS as compared to NHS with 60 and 36 days of survival (p = 0.001) respectively. Higher fecundity was recorded by Ae. albopictus from HS with a mean of 2605 eggs as compared to NHS with only 1140 eggs (p = 0.007). Similar significant differences were also observed for gonotrophic cycle as HS and NHS with 9 and 8 cycles (p = 0.043) respectively. It was found that repeated chemical control affected all biological characteristics except for gonotrophic cycle of Ae. albopictus found in both HS and NHS areas.